2022
DOI: 10.25133/jpssv302022.018
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Literacy and BMI: A Cross-Sectional Study of Suburban Adult Population in Bangladesh

Abstract: Bangladesh is experiencing heightened incidences of obesity among its urban population. This study investigated the relationship between health literacy and body mass index (BMI) among the suburban adult population in the southwestern region of Bangladesh. Data were collected from 196 random participants. Inferential statistics and multinomial logistic regression were used to analyze the data. The BMI was calculated using the World Health Organization standard, and a health literacy index was constructed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…www.nature.com/scientificreports/ Tajdar et al argued that the risk of having components of metabolic syndrome such as obesity, diabetes, and high BP for the subjects with insufficient HL is 1.6 times of those with sufficient HL 27 . According to a study conducted in Bangladesh, higher HL is associated with lower BMI 28 . In addition, Stewart et al found that lower HL was associated with greater nicotine dependence, less knowledge about the health risks related to smoking, and less perceived risk 29 , indicating the significance of preventing CVD among young adults using a health promotion approach to eliminate and modify risk factors and adopt a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Tajdar et al argued that the risk of having components of metabolic syndrome such as obesity, diabetes, and high BP for the subjects with insufficient HL is 1.6 times of those with sufficient HL 27 . According to a study conducted in Bangladesh, higher HL is associated with lower BMI 28 . In addition, Stewart et al found that lower HL was associated with greater nicotine dependence, less knowledge about the health risks related to smoking, and less perceived risk 29 , indicating the significance of preventing CVD among young adults using a health promotion approach to eliminate and modify risk factors and adopt a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this program should consider other healthcare services like monthly health checkups, supplementary nutrition and health-related advice during pregnancy, as these healthcare services are positively associated with improvement of maternal health and reduction of maternal mortality. Alongside the cash transfer program, a health literacy program should be initiated to teach the targeted group on proper healthcare services (Islam et al ., 2022). The authors also prescribe a joint partnership of the government and nongovernment institutions for running the CCT program at the mass level all over Bangladesh.…”
Section: Discussionmentioning
confidence: 99%